Knowledge and Practice on Contraception among Women of Reproductive Age - KC, Heera; Parajuli, Surya Bahadur; Bhattarai, Surakshya; Dhamala, Jiba Nath (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Family planning is a priority programme of the Government of Nepal, with more emphasis on contraception at all levels of the healthcare setting. It advocates the acceptability of contraceptive devices through distribution of Information, Education and Communication materials. Yet studies from various parts of Nepal identified the know-do gap in the use of contraception. The objective of this study was to assess the knowledge and practice of contraception among women of reproductive age of Gramthan rural municipality of Morang, Nepal. Methods A descriptive cross-sectional study was conducted among 384 women in the 15-49 years of reproductive age group from 17 June 2022 to 17 September 2022. The consecutive sampling technique was used for data collection with a semi structured questionnaire via face to face interview. Results The maximum number of participants were Brahmin/Chhetri 118 (30.7%). A majority (35.7%) were of 15-25 years with mean±S.D. =30.4±9.08years. All participants had heard at least one contraceptive method. The majority (80.7%) had heard about the male condoms. Only 34.4 % used family planning methods. Among them, 107(81.1%) were using temporary methods and 25(18.9%) were using permanent methods. The practice of using contraceptive devices declined with increasing age. Conclusions The participants had heard of at least one method of contraceptive, but very less had used any contraceptive devices. Most women were temporary method users. There was a decline in contraceptive use with increasing age.